2015
DOI: 10.1007/s13593-015-0302-5
|View full text |Cite
|
Sign up to set email alerts
|

Weeds for bees? A review

Abstract: Agricultural intensification has led to the decrease of the diversity of wild and domestic pollinators. For instance, honeybees declined by 59 % in 61 years in the USA. About 35 % of major crops in the world depend on pollination services, and 3-8 % of world crop production will disappear without pollinators. Indeed, pollination provides several ecosystem services such as enabling crop and honey productions, regulating weeds and other cultural services. Agricultural intensification has also decreased weed dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
126
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 243 publications
(145 citation statements)
references
References 184 publications
1
126
1
4
Order By: Relevance
“…Improving such habitats may have a lower effect on crop production (i.e. less frequent species are in field margins and are rarely abundant in the field core), but may support other ecological services such as pollination [26,79,80]. Our results also suggest that biodiversity and crop production may be supported in landscapes with less intensively farmed fields according to a land-sharing strategy, although further studies incorporating weed abundance (rather than just richness) need to be conducted.…”
Section: Resultsmentioning
confidence: 78%
“…Improving such habitats may have a lower effect on crop production (i.e. less frequent species are in field margins and are rarely abundant in the field core), but may support other ecological services such as pollination [26,79,80]. Our results also suggest that biodiversity and crop production may be supported in landscapes with less intensively farmed fields according to a land-sharing strategy, although further studies incorporating weed abundance (rather than just richness) need to be conducted.…”
Section: Resultsmentioning
confidence: 78%
“…The decrease in some weeds may be due to the intensive use of external inputs (Marshall et al 2003;Bretagnolle and Gaba 2015). This can be direct effects on weeds (e.g., herbicides, fertilizers) or indirect effects on their pollinators (e.g., insecticides).…”
Section: Reduce External Inputs To Increase Biodiversitymentioning
confidence: 99%
“…They play major functional roles for agricultural ecosystems and their biodiversity and thus have several consequences on ecosystem services, especially pollination (Biesmeijer et al 2006;Bretagnolle and Gaba 2015). Increasing weed abundance can (i) maintain pollinator populations, (ii) ensure pollination services, (iii) increase honey yields and therefore be a benefit for beekeepers, and (iv) improve the sociocultural value of landscape by ensuring the persistence and survival of wild flora (Bretagnolle and Gaba 2015). For instance, some studies have showed the importance of weeds as food resource for insect pollinators, especially bees (Rollin et al 2013;Requier et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations